PENGARUH KECERDASAN EMOSIONAL DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI PT. KAI STASIUN BELAWAN - Oki Harmiansyah; Safrida .; Tri Kartika Yudha; Fauzan Azim (Universitas Islam Islam Sumatera Utara, 2021)
The formulation of the problems in this study are (1) whether there is an influence of emotional intelligence on improving employee performance at PT. KAI Belawan Station. (2) whether there is an influence of motivation on improving employee performance at PT. KAI Belawan Station. (3) whether there is an influence between emotional intelligence and motivation on employee performance at PT. KAI Belawan Station. The purpose of this study is (1) to find out whether there is an influence of emotional intelligence on the performance of employees at PT. KAI Belawan Station. (2) to find out whether there is an influence of motivation on employee performance at PT. KAI Belawan Station. (3) to find out whether there is an influence between emotional intelligence and motivation on employee performance at PT. KAI Belawan Station. The sample in this study were 31 people with data analysis techniques in this study using multiple linear regression analysis. The results of this study explain that emotional intelligence does not have a positive and significant effect on the performance of employees of PT. KAI Belawan Station, while motivation has a positive and significant effect on the performance of PT. KAI Belawan Station. F test results state that emotional intelligence and motivation have a positive and significant effect on the performance of employees of PT. KAI Belawan Station. The determination test shows that 40.2% of employee performance variables can be explained by the variables in this study and the remaining 59.8% can be explained by other variables not included in this study.